Solve 5−6x=−7 .

2 answers

To solve the equation 5-6x = -7, we need to isolate the variable x.
First, we want to get rid of the constant term on the left side, so we can add 7 to both sides of the equation:

5 - 6x + 7 = -7 + 7
12 - 6x = 0

Now, we need to isolate the variable x. To do this, we can subtract 12 from both sides:

12 - 6x - 12 = 0 - 12
-6x = -12

Finally, we divide both sides by -6 to solve for x:

-6x/-6 = -12/-6
x = 2

So the solution to the equation 5-6x = -7 is x = 2.
wrong
Similar Questions
  1. Combine like terms:-3x^2+2x-4x^2-9+6x-2x^2+8 Solve for x: 8x-11= -11x+18 Solve for x: -2(x-5)+7=z-8-5x Solve for x: (x-2)/5 -
    1. answers icon 8 answers
  2. Solve the indicated variable:1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
    1. answers icon 1 answer
  3. Put in the correct orderSolve exponentiation. Solve multiplication and division. Solve operations within parentheses Solve
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions